Kinetic, Isotherm Studies of the Adsorption of the Congo Red Dye by Posidonia Spheroids Plants Sea Balls (PSPSB). (Sebha University Conference Proceedings, 2024)
Please This research investigates the kinetics and isotherms of Congo red dye adsorption using low-cost Posidonia spherical plant sea Balls (PSPSB), without any chemical or physical treatment. The study evaluated some physical properties such as moisture content, and solubility. Moreover, the effect parameters, including pH, adsorbent dose, contact time, and initial dye concentration, were examined for their effects on the adsorption process. The optimal pH for adsorption was found to be 3. The percent removal(%)  of the dye increased with the increasing adsorbent doses and initial dye concentrations until reaching the equilibrium state. The contact time to equilibrium was 20 minutes, and the adsorption capacity maximum reached 49.96 mg/g.  Kinetic reaction results indicated the adsorption process followed a pseudo-second-order reaction model more fit than a first-order model. Isotherm analyses showed the adsorption process fit with Freundlich isotherm, suggesting that the adsorption process is multi-layered and occurs on a heterogeneous surface. The findings confirm that PSPSB are adsorbents effective for removing various pollutants, including dyes and heavy metals, from aquatic environments.